3-in-1 washing machine - Ibrahim, Norshamsiah; Mohd Johari, Ummi Ummairah; Rozaili, Nur Amierah Syafiqah; Jamili, Nur Izzati; Norhisham, Nurul Nazzratul Nazzrah (Academica Press Solutions, 2025)
The difficulty is in addressing Malaysia's lack of comprehensive, timesaving washing solutions for working professionals and families. Even while traditional washing machines are good at cleaning, they take more time to fold and dry clothes. For those with busy schedules who find it difficult to keep their living space neatly orderly, this procedure becomes more difficult. The problem is that modern laundry technologies are disconnected; washing, drying, and folding are often done by hand or with different equipment. In addition to wasting important time, this results in inefficient use of space, particularly in small urban homes. The opportunity exists to develop a laundry solution that combines folding, drying, and washing functions into a single machine. This innovation may improve the user experience, save time, and minimize effort by simplifying the procedure. To meet the demands of a tech- savvy and convenience-focused market, the design may also include clever features like energy efficiency, space-saving processes, and user-friendly controls. In addition to making consumers' everyday life better, this solution would establish a new benchmark for laundry equipment in modern homes.